PENERAPAN SPATIAL DURBIN MODEL (SDM) PADA INDEKS PEMBANGUNAN GENDER DI PULAU SULAWESI - Suaib, Tri Putri Andayani; Junaidi, Junaidi; Fadjryani, Fadjryani (Majalah Ilmiah Matematika dan Statistika, 2022)
The Gender Development Index (GDI) is a development index of the quality of human life that is more concerned with gender status. GDI can be used to determine human development between males and females. This study uses the Spatial Durbin Model (SDM) method. The SDM method was formed due to the spatial influence on the dependent and independent variables. The purpose of this study is to determine the GDI model in Sulawesi Island and the factors that influence it. The factors that have a significant effect on the Gender Development Index (GDI) in Sulawesi Island using the Spatial Durbin Model (SDM) are Life Expectancy, per capita contests, average years of schooling, and labor force participation.Keywords: GDI, AIC, SDMMSC2020: 62H11